Gastric Pylorus Gland Adenoma in a Pug: A Case Report - Sachin Chaudhary; Vikas Jaiswal; Aarti Bhatele; Surbhi K.Tyagi; Vivak Malik (The Indian Veterinary Journal, 2026)
A 1.5-year-old female Pug with a history of chronic intermittent vomiting revealed multiple polypoid growths in the pyloric region of the stomach on endoscopic examination. Cytology revealed the presence of cohesive cells with a round nucleus and prominent nucleoli, coarse chromatin material. The masses were removed by open surgery, and samples were processed for histopathology, which showed multiple layers of atypical epithelial cells exhibiting areas of malignancy and the absence of an apical mucin cap. Alkaline phosphatase was the only hemato-biochemical parameter found to be increased significantly. Based on the above findings, the case has been concluded as a pyloric gland adenoma.